1992
DOI: 10.1002/hc.520030315
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization reactions of ω‐tosyloxy‐1‐alkynyl‐ and ω‐tosyloxy‐1‐alkenylborates and their ω‐halo analogues

Abstract: The reaction of trialkylboranes with wtosyloxy-l-lithio-1-alkynes can induce transfer of a n alkyl group froiii the boron atom to the alkynyl carbon atom with concomitant formation of four-through

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A related reaction has been reported by Negishi (Scheme ) in which the reaction of tosylvinylborane 5 with 1 equiv of n -butyllithium gave the alkene products 6 and 7 . However, the alcohol 4 was not reported.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…A related reaction has been reported by Negishi (Scheme ) in which the reaction of tosylvinylborane 5 with 1 equiv of n -butyllithium gave the alkene products 6 and 7 . However, the alcohol 4 was not reported.…”
Section: Resultsmentioning
confidence: 68%
“…Modified from the procedure by Negishi, the reaction of ( E )-6-((4 S ,5 S )-3,4-dimethyl-5-phenyl-1,3,2-oxazaborolidin-2-yl)hex-5-enyl 4-methylbenzenesulfonate 16 with methyllithium is representative: To a stirred solution of the oxazaborolidine (0.34 g, 0.80 mmol) in 5 mL of THF at −78 °C, 3 equiv of methyllithium (1.5 mL, 1.6 M) was added dropwise. After 0.5 h, it was slowly brought to rt and stirred for a total of 3 h. It was oxidized by adding 3 M NaOH (0.4 mL, 1.2 mmol) followed by 30% H 2 O 2 (0.50 mL, 4.4 mmol) and heated at 50 °C for 1 h. Ten milliliters of 1 M HCl was added after cooling, and the mixture was extracted three times with 10 mL ether, washed with brine, and back-extracted with ether.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that boronates react with electrophiles such as haloalkanes and aldehydes at the β position with 1,2-migration of alkyl ligands (eq 1) . An intramolecular version of such a reaction leading to exo-type cyclization products was also reported (eq 2). , We report herein that alkynyllithiums bearing a remote leaving group also undergo an exo-type cyclization to give cycloalkylidene carbenes (Scheme ). The study demonstrates a potential reactivity of alkynylmetals other than alkynylate complexes at the β position.…”
mentioning
confidence: 66%
“…They react with a variety of electrophilic reagents generally at the carbon α to the metal atom. Nevertheless, some alkynylmetals, specifically alkynylboronates , and -zincates, are known to react at the β position . It was reported that boronates react with electrophiles such as haloalkanes and aldehydes at the β position with 1,2-migration of alkyl ligands (eq 1) .…”
mentioning
confidence: 99%
“…Alkynylmetal ate complexes such as alkynylboronates , and -zincates are known to react at the β position with simultaneous migration of the ate ligand to the α position. That alkynylmetals (M = Li, Na, K) also exhibit nucleophilic reactivity at the β position was recently disclosed .…”
mentioning
confidence: 99%